Health Benefits and Overuse Risks of Cycling: Biomechanical Mechanisms, Injury Patterns, and Evidence-Based Preventive Strategies - Wojciechowicz, Marek; Rogiński, Miłosz; Brzęcka, Marta; Rogiński, Stanisław; Krupiniewicz, Karol; Suchcicki, Mariusz; Rogiński, Krzysztof; Chojnowski, Łukasz; Mazurek, Katarzyna; Dominiczak, Anna (Quality in Sport, 2026)
Background. Cycling is widely used for active transport and recreation and is associated with favourable long-term health outcomes. At the same time, cycling-related harm includes traumatic injuries and overuse conditions, and the clinical burden may be underestimated in routine surveillance. Aim. To summarise health benefits alongside overuse risks and to integrate biomechanical mechanisms, injury patterns, and practical prevention and rehabilitation strategies. Material and Methods. This manuscript is a narrative review; evidence was synthesised narratively, with reporting transparency informed by PRISMA 2020 and qualitative appraisal of systematic reviews supported by AMSTAR 2. Results. The included evidence supports associations between cycling and lower all-cause mortality and favourable cardiometabolic outcomes, including patterns consistent with reduced type 2 diabetes risk across cycling-volume categories. Biomechanical studies highlight modifiable factors that may influence kinematics and internal loading, including cadence/workload, saddle height, cleat alignment, posture and hand position, and vibration-related exposure. Prevention sources support multi-component approaches (e.g., fit-related adjustments, symptom-focused mitigation, strengthening/supportive interventions, and load-management concepts). Rehabilitation sources describe cycling-based modalities across heterogeneous clinical contexts with condition-specific outcomes and comparators. Conclusions. In this reference set, cycling is associated with lower all-cause mortality and favourable cardiometabolic outcomes, although most long-term data are observational. The greatest net benefit is likely when participation is paired with safety measures and progression, supported by modifiable biomechanics and multi-component prevention and rehabilitation strategies, and injury evidence underscores the importance of trauma risk reduction, including helmet-related safety in children and adolescents.